School Community Empowerment as A Minority Group in Republic Gubuk Library - Inawati, Inawati; Dewi, Amalia Nurma; Setiawan, Setiawan; Martutik, Martutik; Rizqi, Aminah; Azizah, Nur; Hasna, Natasya (Edulib, 2022)
This study aims to analyze the form of empowerment of the dropout community as a minority group in Society-based Library Republik Gubuk. The method used in this research is qualitative data analysis with a case study approach. Data were collected using interview techniques and direct observation at Society-based Library Republic Gubuk. The results of the study showed that several work programs of Society-based Library Republik Gubuk in empowering minority groups, especially children who dropped out of school, by providing space to be creative and innovate according to their respective interests and talents as human resource management activities to have skills and be able to compete. Along with the times. The Society-based Library Republik Gubuk work program provides training in honing creativity as a provision in improving skills based on groups of interest. These activities are called "Preman Mengajar". Preman Mengajar is a work program that provides a forum for empowering school dropouts to develop their abilities and skills in the arts and culture, such as making the Jabung Malangan mask, the local culture of the Jabung area. Making the masks is aimed at preserving local culture and being used as a result of recycled waste materials in which to hone the skills of carving, design, creativity, and others. Apart from that, the Preman Mengajar activity program has also been developed by Society-based Library Republik Gubuk by collaborating with schools in the surrounding environment in the form of providing opportunities for these minority groups to get to know the educational background through the introduction of Jabung local culture to students in local content subjects. In addition to teaching activities in formal schools, these minority groups are also allowed to exchange opinions and provide learning guidance from one hut to another.